Biological inoculants and chemical fertilizers application produce differential effects on rhizobacterial community structure associated to peanut (Arachis hypogaea L.) and maize (Zea mays L.) plants - Anzuay, María Soledad (2023)
The use of biological inoculants in replacement of the application of chemical fertilizers is a desirable strategy taking into account it is more sustainable and economically less costly. Considering that agricultural practices can produce effects on soil microbial communities associated to the plant crops, the objective of this study was to analyze and compare the effect of these two practices on the structure of the rhizobacterial community of peanut and maize plants. For this purpose, microcosm assays were performed in which peanut and maize plants were inoculated individually with native peanut phosphate solubilizing strains or chemical fertilized with phosphorus, nitrogen, zinc and sulphur. At the beginning and at the end of the assays, samples of rhizospheric soil DNA were obtained and the structure of the rhizospheric bacterial community was analyzed by high-throughput sequencing of the 16S rRNA gene by using Illumina MiSeq platform. The results obtained indicated that the structures of the rhizospheric bacterial communities were different depending on plant type. It was possible to observe changes with respect to the initial bacterial structure in all taxonomic levels analyzed of all treatments. The more notorious structural changes of bacterial community were observed in those rhizospheres exposed to chemical fertilizers, mainly in soil samples associated to maize plants. The rhizospheric bacterial community of peanut showed to change mainly with plant growth. In conclusion, the rhizobacterial community structure is highly dynamic and influenced by different factors such as type of plant, the fertilizer input and bio-inoculant applied.